Studies on Placing and Mixing of a Normal Soil in Limestone Minespoil on the Performance of Two Tree Species - Dadhwal, K. S.; Singh, Bijendra; Narain, Pratap (Indian Forester, 1993)
Studies were conducted for 80 weeks in trapezoidal pots of 40 cm sides and depth to evaluate the effect of top placing and mixing of normal soil in limestone mine spoil/debris on the performance of L. leucocephala and B. retusa. Placement of 30 cm normal soil with debris was found best for L. leucocephala and mixing the same amount was optimum for B. retusa as revealed by height, basal diameter, crown spreads biomass yield and some root characters. Mixing or placement of 15 cm normal soil with debris was also beneficial for both the species but 5 cm treatment did not show much superiority over debris alone. Higher N and P content was observed in leaves of both the species as compared to roots and shoots. The distribution of K was uniform in B. retusa while it was more in leaves of L. leucocephala followed by roots and then shoots. Total uptake of nutrient followed the dry matter yield pattern. Maximum distribution of roots was observed in 5-15 and >15 cm layers after 80 weeks.